Reconciling global-model estimates and country reporting of anthropogenic forest CO2 sinks - Grassi, Giacomo; House, Jo; Kurz, Werner A; Cescatti, Alessandro; Houghton, Richard A; Peters, Glen P; Sanz, Maria J; Raul Abad Viñas; Alkama, Ramdane; Arneth, Almut; Alberte Bondeau; Dentener, Frank; et al. (Nature climate change, 2018)
Achieving the long-term temperature goal of the Paris Agreement requires forest-based mitigation. Collective progress towards this goal will be assessed by the Paris Agreement’s Global stocktake. At present, there is a discrepancy of about 4 GtCO2 yr−1 in global anthropogenic net land-use emissions between global models (reflected in IPCC assessment reports) and aggregated national GHG inventories (under the UNFCCC). We show that a substantial part of this discrepancy (about 3.2 GtCO2 yr−1) can be explained by conceptual differences in anthropogenic forest sink estimation, related to the representation of environmental change impacts and the areas considered as managed. For a more credible tracking of collective progress under the Global stocktake, these conceptual differences between models and inventories need to be reconciled. We implement a new method of disaggregation of global land model results that allows greater comparability with GHG inventories. This provides a deeper understanding of model–inventory differences, allowing more transparent analysis of forest-based mitigation and facilitating a more accurate Global stocktake.